Boosting the Immune System for HIV Cure: A γδ T Cell Perspective - Mann, Brendan T.; Sambrano, Edward; Maggirwar, Sanjay B.; Soriano-Sarabia, Natalia (Frontiers in Cellular and Infection Microbiology, 2020)
The major barrier to HIV cure is a population of long-lived cells that harbor latent but replication-competent virus, are not eliminated by antiretroviral therapy (ART), and remain indistinguishable from uninfected cells. However, ART does not cure HIV infection, side effects to treatment still occur, and the steady global rate of new infections makes finding a sustained ART-free HIV remission or cure for HIV-seropositive individuals urgently needed. Approaches aimed to cure HIV are mostly based on the “shock and kill” method that entails the use of a drug/compound to reactivate latent virus paired together with strategies to boost or supplement the existing immune system to clear reactivated latently infected cells. Traditionally, these strategies have utilized CD8+ cytotoxic lymphocytes (CTL) but have been met with a number of challenges. However, enhancing innate immune cell populations, such as  T cells, may provide an alternative route to HIV cure.  T cells possess anti-viral and cytotoxic capabilities that have been shown to directly inhibit HIV infection and specifically eliminate reactivated, latently infected cells in vitro. Most notably, their access to immune privileged anatomical sites and MHC-independent antigen recognition may circumvent many of the challenges facing CTL based strategies. In this review, we discuss the role of  T cells in normal immunity and HIV infection as well as their current use in strategies to treat cancer. We present this information as means to speculate about the utilization of  T cells for HIV cure strategies and highlight some of the fundamental gaps in knowledge that require investigation.